Fenômenos de Exchange Bias e Exchange Spring em Tricamadas NiFe/IrMn/Co: a Influência da Textura Cristalográfica da camada IrMn - Merino, Isabel Liz Castro (2013)
In the present work, a systematic investigation, through structural and magnetic characterizations, is discussed regarding the influence of the crystallographic texture on the Exchange Spring observed in the NiFe/IrMn/Co trilayer deposited at room temperature with Magnetron Sputtering technique. Using X-ray diffraction, it was shown that NiFe, IrMn and Co layers have texture oriented fcc [111], when Ta seed layer deposited, and there was no of other types of orientations. For samples grown on Cu seed layer, beyond majority [111]-fcc, types of [200] and [220] orientations are also present in the diffraction patterns of the NiFe/IrMn/Co heterostructures. From X-ray reflectivity, it was determined that the Cu-system has much high Si/Cu interface roughness (Si/Cu, rms = 2.8 nm) than that of Ta (Si/Ta, rms = 0.2 nm). Combining results from the combination of DC magnetization and ferromagnetic resonance techniques, performed at room temperature, it is provided a planar magnetic anisotropy and an understanding of the Exchange Bias (unidirectional exchange coupling at the NiFe/IrMn and IrMn/Co interfaces) and the Exchange Spring effects in NiFe/IrMn/Co heterostructures. DC magnetization data suggest that the Exchange Spring exists before the field cooling protocol (unidirectional anisotropy induction). The Exchange Spring phenomenon (consequently the IrMn spins structure) was shown to be strongly dependent on the degree of [111] texture in the IrMn layer, which is, in turn, dependent on the seed layer (Cu or Ta) deposited on Si(100) substrate. It has also been demonstrated, a posteriori, that a field cooling of 10 Oe is sufficient to set the Exchange Bias effect on both interfaces (NiFe/IrMn and IrMn/Co). In addition, it was observed that the highest Exchange Bias field occurs when an unstressed L12 IrMn structure is stabilized at 6-8 nm IrMn thickness interval. Due to different degree of texture (interface roughness may also be present), it can be shown that exchange bias effect is distinct for Ta and Cu systems. For the systems where unidirectional anisotropy is set, it has been demonstrated that for increasing IrMn thickness (from 5 up to 30 nm), the magnetic coupling angle between NiFe and Co magnetizations increases for the Cu-system, while it is reduced in the Ta-system. These results were explained considering: (i) the measured different anisotropies of the Co and IrMn layers induced by the [111] texture and (ii) distinct Exchange Bias field in NiFe/IrMn and IrMn/Co interfaces in both systems. It was shown that the coupling angle is strongly correlated by both Exchange Bias and Exchange Spring effects. Through resonant magnetic scattering measurements found a presence of reversible non-compensated under the action of magnetic field for both systems with unidirectional anisotropy (clearer effect for the Cu-system). Furthermore hysteresis loops through element selective obtained by this technique proved the presence of Exchange Spring effect in Cu system, even prior to applying cooling field.